The Business Resilience of Small Micro Medium Enterprise During Pandemic Time - Dewi Kurniaty; Iin Mayasari; Iyus Wiadi; Ahmad Azmy; Adrian Wijanarko; Ritzka Yauma Putri Driarkoro (Research Synergy Foundation, 2022)
Due to the pandemic in 2020, micro, small and medium enterprises (MSMEs) experienced poor performance. This change creates impacts on business management to survive in an uncertain situation. This study analyzed the Leverage Secondary Association's (LSA) concept in business resilience to maintain the business long-term. This research focuses on the partnership elements: people, places, things, and collaboration with other parties and suggests optimized programs to support future business sustainability. This research uses a qualitative approach and develops a list of interview questions based on elements of LSA. The results were analyzed using data reduction, categorization, and synthesis methods. The interview involved three MSME owners from the tourism sector and small business retail. The result of the study has explored some primary issues in employees, resources, and market expansion. In Peoples, the LSA strategy encourages the company to empower the employee and enhance the sense of belonging to the company. In Things, by developing a partnership with other parties, the business maintains the supply of raw materials and stability of the prices. In Places, partnership's sustainability, especially with the distributors at the national and international level, opened the opportunity for market expansions.